Cervical HPV natural history among young Western Cape, South African women: The randomized control EVRI Trial. Issue 1 (January 2016) - Sudenga, Staci L.; Torres, B. Nelson; Botha, Matthys H.; Zeier, Michele; Abrahamsen, Martha E.; Glashoff, Richard H.; Engelbrecht, Susan; Schim Van der Loeff, Maarten F.; Van der Laan, Louvina E.; Kipping, Siegfried; Taylor, Douglas; Giuliano, Anna R.
Summary: Objective: The objective of this analysis was to assess human papillomavirus (HPV) infection persistence and incidence 7-months post-enrollment by HPV vaccine study arm (vaccine or placebo). Methods: HIV-negative, sexually active women aged 16–24 years in the Western Cape, South Africa, were enrolled in the EVRI Trial and were randomized to receive 4-valent HPV vaccine or placebo. Cervical specimens were collected at enrollment and at the 7-month visit and were genotyped for HPV. HPV prevalence, persistence, and incidence were calculated. Prevalence ratios and odds ratios were calculated to assess factors associated with a prevalent and incident HPV infection. Results: HPV incidence rates were marginally higher for the placebo group (n = 163) compared to the vaccine group (n = 169). A large proportion of the prevalent high-risk (HR-HPV) HPV types (49%) persisted over the 7-month period in both arms. Prevalent HR-HPV infection was significantly associated with a prevalent gonorrhea infection and detection of Herpes simplex type 2 antibodies. Incident HR-HPV infection was significantly associated with abnormal cervical cytology at enrollment and younger age. Conclusions: Women living in geographic areas, such as southern Africa, at high-risk for HPV need to receive HPV vaccination at a very young age to maximally prevent infection and subsequent disease.